Wirtlich handeln in Sozialer Arbeit Die ökosoziale Theorie in Revision - Wendt, Wolf Rainer (Theorie, Forschung und Praxis der Sozialen Arbeit, 2018)
In the science of social work, there are different approaches to explaining what socio-professional action is concerned with, how it is structured and what it has to focus on. Ecosocial theory has been part of this for about 40 years now. It represents a conceptual foundation of social work, which starts from the household of common life and its maintenance. Against the background of the ongoing discussion about the theoretical basis of social work, the author subjects the eco-social approach he developed to a revision.